Application of life cycle assessment approach to deliver low carbon houses at regional level in Western Australia - Lawania, K.; Biswas, Wahidul (Springer, 2017)
Purpose: Australian building sector contributes 23% of the total greenhouse gas (GHG) emissions. This is particularly important for Western Australia (WA) as the houses here are made of energy- and carbon-intensive clay bricks. This research has utilized life cycle assessment (LCA) approach and cleaner production strategies (CPS) to design low-carbon houses in 18 locations in regional WA. Methods: An integrative LCA analysis of clay brick house has been conducted by incorporating energy efficiency rating tool (i.e., AccuRate) to capture the regional variation in thermal performance of houses in 18 locations in WA under five climatic zones. The data bank provided information on energy and materials for mining to material production, transportation of construction materials to the site of construction, and construction stages, while an energy rating tool has been utilized to generate location-specific information on energy consumption during use stage for developing a life cycle inventory for estimating life cycle GHG emissions and embodied energy consumption of a typical 4 × 2 × 2 detached house (i.e., 4 bed rooms, 2 bathrooms, and 2 cars/double garage). This approach has enabled us to determine the location-specific hotspot of a house in order to select suitable CPS for achieving reduced level of GHG emissions and embodied energy consumption. Results and discussion: Except for two hottest locations, the average life cycle GHG emissions and embodied energy consumption of houses at 16 locations in regional WA have been estimated to be 469 t of CO2 equivalent (or CO2 e-) and 6.9 TJ, respectively. Home appliances and water heating have been found to be the top two hotspots. The CPS options, including rooftop solar photovoltaic panels (PV), solar water heaters (SWH) integrated with gas based water heaters, cast in situ concrete sandwich wall, fly ash as a partial replacement of cement in concrete, and polyethylene terephthalate (PET) foam made of post-consumed polyethylene terephthalate bottles, have been considered to reduce GHG emissions and embodied energy consumption of a typical house in18 locations in regional WA. Excluding above two hottest locations, these CPS provide an opportunity to reduce GHG emissions and embodied energy consumption per house by an average value of 320 t CO2 e- and 3.7 TJ, respectively. Conclusions: Considering the alarming growth rate of the housing industry in WA, the incorporation of optimum house orientation, rooftop solar PV, roof top SWH, cast in situ sandwich wall, partial replacement of cement in concrete with fly ash, and PET foam insulation core could reduce the overall GHG emissions and embodied energy consumption associated with the construction and use of clay brick wall house which in turn will assist in achieving Australia’s GHG emission reduction target by 2050. The findings provide useful data for architects, designers, developers, and policy makers to choose from these CPS options based on existing resource availability and cost constraints.